Warriors. Tigerstar & Sasha. #1 : Into the woods - Hunter, Erin.; Jolley, Dan.; Hudson, Don, (Illustrator) (Los Angeles : Tokyopop ; New York : HarperCollins, 2008)
Forced to leave her home, Sasha quickly grows tired of life on her own but she is not sure that joining ShadowClan, led by Tigerstar, would be a better choice.
3-6
3.2
Keywords: Graphic novels; Cats -- Fiction; Fantasy; Cats -- Fiction; Adventure and adventurers -- Fiction; Fantasy; Graphic novels